APPROPRIATION AND USE OF URBAN COAST OF BELÉM-PARÁ: AMAZON GATE IN QUESTION - Araújo Júnior, Antônio Carlos Ribeiro (Revista do Departamento de Geografia, 2013)
The Recovery Program Urban and Environmental Watershed of New Road (PROMABEN) in the southern portion of the city of Belém (PA) has as one of its fronts work of road infrastructure jobs, which seek the opening of the border, putting the city facing the Guamá river since its growth was back to him.This "back to the river," by opening the waterfront is known as the Amazon Portal. To this end, we seek to understand the integrity of PROMABEN focusing for the process historical and geographical of appropriation and land use in coastal belenense and possible conflicts generated thence, with reference to the Watershed of New Road (BHEN). The study was conducted based on bibliographic and documentary, as well as reports of residents near the Amazon Gate analyzed based on means of circulation (newspapers, websites, etc.), for a holistic understanding biased in systemic method.